Preparation of Novel Aromatic‐Aliphatic Poly(ketone ester)s through Condensation of Biomass‐Derived Monomers. Issue 23 (23rd October 2018) - Chen, Qin; Ren, Tianhua; Chai, Yang; Guo, Yuanlong; Ingram, Ian D. V.; North, Michael; Xie, Haibo; Kent Zhao, Zongbao
Abstract: Abstract : Novel unsaturated and saturated monomers with a hydroxyl group and a carboxylic group via aldol condensation reaction of lignin‐derived aromatic aldehydes with levulinic acid were prepared through organocatalysis and hydrogenation, respectively. The catalytic process was optimized and the structure of the monomers were full characterized. The as‐prepared monomers were ready for the subsequent condensation polymerization to achieve a serial of novel full biobased poly(ester ketone)s. The chemical‐physical properties of the poly(ester ketone)s were evaluated. This provides a green upgrading strategy to prepare sustainable synthetic polymers from building blocks available on a large scale using a catalytic biorefinery approach. Abstract : Keeping it green : Biobased poly(ester ketone)s were prepared through aldol condensation of aromatic aldehydes obtainable from lignin with levulinic acid available from cellulose and hemicellulose via green catalysis and polycondensation.